Sampah dan Ekologi Perkotaan: Telaah Ekokultural pada Naskah Lakon “Bagian-Bagian Hormat (dan) Sampah” Karya Afrizal Malna - Khothibul Umam (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
This research is a library research with the object of the play script "Bagian-bagian Hormat (dan) Sampah" by Afrizal Malna. This play script contains environmental phenomena, pollution, consumerism and urbanization. This play script uses unconventional forms in the form of presentation. The script is divided into six parts by using an essay in the form of an essay that contains descriptions of the scene that will be demonstrated by the actors and various artistic aspects that appear in the show. The text will be studied with Ecocultural theory. Ecocultural Criticism is a theory used to examine the relationship between literature and the environment. Ecoculture takes the point of view of "the earth as the center" in the approach of literary studies. The results of this study indicate that the Indonesian economy which was built with various kinds of capital and massive foreign investment created industrialization and triggered consumerism. In addition, other problems arise such as pollution and urbanization. The play script "Bagian-bagian Hormat (dan) Sampah" portrays all these phenomena and presents them in the performance text. With an ecocultural study, it can be found a link between the social context that occurs and the text presented in "Bagian-bagian Hormat (dan) Sampah".